"Es mi voz": A Survey of Early Latina Writers in Latino Literature Anthologies - Cresci, Karen Lorraine (2021)
The production of anthologies is the result of a complex interplay of factors: the needs of teachers, the critical evaluation of editors and scholars, copyright limitations, and the demands of the marketplace. Determining the scope and contents of an anthology also has its challenges, such as genres, themes, authors, and dates. While this is true in general for anthologies, considerations for Latino literature anthologies are met with unique cultural specificities...